2014
DOI: 10.1080/21683565.2013.870101
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Participatory Varietal Selection: A Sustainable Crop Improvement Approach for the 21st Century

Abstract: Participatory variety selection (PVS) for the selection and testing of salt tolerant varieties/genotypes and breeding accessions of rice was conducted at Central Soil SalinityResearch Institute, Regional Research Station, Lucknow, Uttar Pradesh, India from 2001 to 2007. This aimed to identify high yielding, adaptable, and acceptable rice cultivars for sodic soils through farmers' participation. Typically, plant breeders develop varieties isolated from active farmers and release varieties that are most producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 10 publications
1
36
0
6
Order By: Relevance
“…On peut qualifier cette démarche de participative et responsabilisante. Elle rejoint celles préconisées ces dernières années par plusieurs auteurs pour le transfert des technologies agricoles (par exemple, Beaudoux et al, 1995 ;Singh et al, 2014 ;Tackie et al, 2009).…”
Section: Discussionunclassified
“…On peut qualifier cette démarche de participative et responsabilisante. Elle rejoint celles préconisées ces dernières années par plusieurs auteurs pour le transfert des technologies agricoles (par exemple, Beaudoux et al, 1995 ;Singh et al, 2014 ;Tackie et al, 2009).…”
Section: Discussionunclassified
“…RYMV resistance was not identified as a selection criterion since the incidence of the disease was low at all locations during the season. Joshi and Witcombe (2008), Wopereis et al (2009),Singh et al (2014 and Angarawai et al (2016) identified farmer participatory varietal selection as the best approach for exposing farmers to cultivars and improving adoption rates.…”
Section: Resultsmentioning
confidence: 99%
“…Masalah tersebut diduga salah satunya disebabkan oleh sangat beragamnya preferensi petani terhadap suatu varietas baik itu dari morfologi tanaman maupun mutu beras yang dihasilkan (Almekinders dan Elings, 2001;Singh et al, 2013). Preferensi yang sangat beragam antar daerah atau bahkan antar petani membutuhkan ketersediaan pilihan varietas yang lebih beragam dari pemulia.…”
Section: Pendahuluanunclassified
“…Nilai preferensi (preference score) dan hasil gabah genotipe padi gogo di lahan petani Cianjur, Jawa Barat pada MH 2012-2013 Panen dilakukan setelah pelaksanaan seleksi partisipatif. Hasil pengambilan sampel gabah kering giling menunjukkan galur B12790E-TB-2-1 memiliki hasil gabah tertinggi (6.8 t/ha), lebih tinggi dibandingkan semua varietas pembanding.…”
Section: Penampilan Agronomi Dan Preferensi Petani Terhadap Galur Danunclassified
See 1 more Smart Citation